Prevalence of Prolonged QT Interval In Patients With Chronic Liver Disease: Prolonged Qt Interval in Patients with Chronic Liver Disease - Kanwal, Marium; Hussain, Waqar; Soomro, Aqsa; Aijaz, Razia; Khalique, Sumon; Sadaf, Maliha (Pakistan Journal of Health Sciences, 2022)
The incidence of QT prolongation in CLD patients is greater than 45% compared to approximately 5% in the general population. Multiple researches have revealed that end-stage liver disease is related with a variety of changes in electrophysiological parameters; especially in our population, a higher incidence of QT interval prolongation is observed. Prolonged QT intervals in chronic liver disease patients are related with augmented mortality and morbidity. Objective: To determine the frequency of QT prolongation in patients with chronic liver disease. Methods: A cross-sectional and descriptive study. 96 total patients aged 20-85 years of both sexes with chronic liver disease (CLD) were included. Patients with a history of coronary artery disease and the use of any anti-arrhythmic medication were excluded from the study. The 12-lead ECG was performed and interpreted by an electrophysiologist with over five years of experience. The Bazett-based QT interval (QTc) was automatically obtained using a computerized electrocardiograph to avoid inter-observer variability. Results: 20 to 60 years was the patients age in this study, with 39.44 ± 9.91 years of mean age. The maximum patients, 86 (89.58%), were 20-40 years of age. Among the 96 patients, 17 (17.71%) were female and 79 (82.17%) were male, with a M: F ratio of 1.3: 1. While the incidence of QT prolongation was found in 47 (48.96%) patients, 49 (51.04%) patients did not have QT prolongation. Conclusions: In this study it was found that the frequency of QT prolongation is quite high in patients with chronic liver disease